Respuesta :

Answer:

[tex]P(t) = 104.267\ millions[/tex]

Step-by-step explanation:

The exponential growth formula is

[tex]P(t) = Ae^{kt}[/tex]

Where

A is the main coefficient and represents the initial population.

e is the base

k is the growth rate

t is time in years.

Let's call t = 0 to the initial year 1993.

At t = 0 the population was 94 millions

Therefore we know that:

[tex]P(0) = 94[/tex] millions

After t = 6 years, in 1996, the population was 99 millions.

Then [tex]P(6) = 99[/tex] million.

Now we use this data to find the variables a, and k.

[tex]P(0) = 94 =Ae ^{k(0)}\\\\94 = A(e ^ 0)\\\\A = 94[/tex].

Then:

[tex]P(6) = 94e^{k(6)}\\\\99 = 94e ^{6k}\\\\\frac{99}{94} = e^{6k}\\\\ln(\frac{99}{94}) = 6k\\\\k = \frac{ln(\frac{99}{94})}{6}\\\\k =0.008638[/tex]

Finally the function is:

[tex]P(t) = 94e^{0.008638t}[/tex]

In the year 2005:

[tex]t = 2005-1993\\\\t= 12\ years[/tex]

So the population after t=12 years is:

[tex]P(t) = 94e^{0.008638(12)}[/tex]

[tex]P(t) = 104.267\ millions[/tex]

Answer:

104 million

Step-by-step explanation:

We are given that a country's population in 1993 was 94 million and in 1999, it was 99 million.

We are to estimate its population in 2005.

Let P(t) denote the population at t years after 1993, then:

P(0) = 94 million  

P(6) = 99 million

[tex]P(t) = P(0) e^{(k t) }[/tex]

So [tex]P(6) = P(0) e^{(6 k) }[/tex]

[tex]99 = 94 e^{(6 k) }[/tex]

[tex]e^{(6 k)} = \frac{99}{94}[/tex]

[tex]6k=ln(\frac{99}{94} )[/tex]

[tex]k=ln(\frac{\frac{99}{94}}{6}  )[/tex]

[tex]k=0.0086375[/tex]

Now since we have found the value of [tex]k[/tex], we can estimate the population in 2005:

t = 2005 - 1993 = 12

P (12) = [tex]P(0) e^{( 12 k)} = 94 e^{( 12 (0.0086375) ) }[/tex] = 104.266 million